STATUS OF CHOCOLATE MAHSEER OF RIVER BARAK WITH A NOTE ON ITS MORPHOMETRY AND MERISTICS - KAR, DEVASHISH; BARBHUIYA, ANJAM HUSSAIN (Journal of the Inland Fisheries Society of India, 2022)
The fish fauna of North East India is one of the richest in India and especially noted for the torrential species. The river Barak with more than 11 major perennial tributaries creates an important field of study on these rheophilic forms. Of these, the species belonging to the genus Tor Gray andÂ Neolissochilus Rainboth, popularly called â€˜Mahseerâ€™ or large scaled Indian carps are the prized fish of the region. Anglers regard them as one of the important sport fishes, making them a source of recreation to innumerable tourists, anglers and naturalists.